Range expansion as an explanation for introgression in European wildcats. (February 2018) - Nussberger, B.; Currat, M.; Quilodran, C.S.; Ponta, N.; Keller, L.F.
Abstract: Introgression between domestic and wild taxa is a conservation issue because it can lead to the genetic extinction of wild taxa. Understanding the causes of introgression is thus a crucial task for conservation biologists. Here we provide evidence from biparentally, paternally and maternally inherited genetic markers in hybridizing European wildcats ( Felis silvestris silvestris ) and domestic cats ( Felis silvestris catus ) that one cause of introgression can be range expansion of the threatened species. We analyzed 68 autosomal, two Y-chromosomal and four mitochondrial diagnostic single nucleotide polymorphisms, and a sequence of 384 base pair of mitochondrial DNA, in 224 wild- and domestic cats from the Jura region of eastern Switzerland and western France. Using Bayesian estimation approaches, we found more gene flow from domestic cats to wildcats than vice versa (0.017 and 0.003 migrants per generation). Introgression of maternally inherited markers was higher than of paternally inherited markers. To test if these observed introgression patterns might be explained by wildcat expansion, we simulated neutral genetic data under various models of hybridization including spatial features such as range expansion. The most likely scenario represented an expansion of wildcats into domestic cat range. We also explored the geographic distribution of wildcats and hybrids. In comparison to wildcats, hybrids were found closer to the edge of the wildcat distribution range. Overall, the patterns we observed are compatible with the hypothesis that introgression is caused by wildcat range expansion, rather than by domestic cat invasion of wildcat habitat. That the threatened European wildcat is expanding is a positive sign, but careful monitoring of introgression and its fitness consequences is needed to ensure that the wildcat does not go genetically extinct in the generations to come.